A systematic review of female badminton talent identification: Implications for development - Komari, Amat; Arzhan Hidayat, Rezha; Ihsan, Fadli; Wahyu Arga, Muhammad; Iswanto, Ari; binti Abdul Razak, Norsilawati (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to systematically review female badminton talent identification methods and their implications for athlete development. The review analysed literature on talent identification criteria, including physiological, psychological, and social factors. The materials used were articles published in international journals from various databases such as Scopus, PubMed, and Web of Science. The methodology of this study utilised a systematic review approach based on the PRISMA guidelines. This review’s main findings indicate that identifying female badminton talent involves a multidimensional assessment, which includes physical measurements such as strength and agility, psychological aspects such as motivation and mental toughness, as well as social factors such as family support and access to training. However, research shows gaps in gender-sensitive approaches and limitations of research in developing countries. The practical implication of these findings is the importance of developing more specific talent identification methods for women, taking into account physiological and psychological differences relative to men. This study concludes that despite significant efforts in talent identification, more research is needed to develop more accurate and applicable tools for female badminton athletes and expand the scope of future research. earch.